The Influence of Age and Sex on Cervical Spinal Alignment Among Volunteers Aged Over 50. Issue 19 (1st October 2015) - Oe, Shin; Togawa, Daisuke; Nakai, Keiichi; Yamada, Tomohiro; Arima, Hideyuki; Banno, Tomohiro; Yasuda, Tatsuya; Kobayasi, Sho; Yamato, Yu; Hasegawa, Tomohiko; Yoshida, Go; Matsuyama, Yukihiro
Abstract : Study Design: Large cohort study of volunteers aged over 50. Objective: To investigate influence of age and sex on cervical sagittal alignment among volunteers aged over 50. Summary of Background Data: Few large-scale studies have described normative values in cervical spine alignment regarding age and sex among volunteers aged over 50. Methods: The study cohort included 656 volunteers aged 50 to 89 years. Pelvic tilt, sacral slope, pelvic incidence, lumbar lordosis, pelvic incidence−lumbar lordosis, thoracic kyphosis, T1 slope (T1S), cervical lordosis (CL), C7 sagittal vertical axis (C7 SVA), C2−C7 SVA, and T1S−CL were measured using whole spine and pelvic radiographs taken in the standing position. Health-related quality of life was assessed using the EuroQOL (EQ-5D) standardized instrument for measurement of health outcome and Oswestry Disability Index. Results: There were 36 subjects aged 50 to 59 years, 174 aged 60 to 69 years, 311 aged 70 to 79 years, and 135 aged 80 to 89 years. Average T1S for each decade was 32°, 31°, 33°, and 36° for males, and 28°, 29°, 32°, and 37° for females, respectively. Average C2–C7 SVA was 25, 28, 34, and 35 mm for males, and 20, 21, 22, and 28 mm for females, respectively. C2–C7 SVA 40 mm or more, T1S 40° or more, and T1S–CL 20° or more pertaining to EQ-5D were significantly worse in other cases. Conclusion: C2–C7 SVA was significantly greater in males among all age groups, particularly among those with C2–C7 SVA of 40 mm or more [males, 69% (82/118) vs. females, 33% (36/118)]. Sagittal parameters of cervical spine were significantly worse in males than females. C2–C7 SVA, T1S, and T1S–CL negatively influenced EQ-5D. These results help to explain the greater prevalence of cervical spondylotic myelopathy among elderly males. Level of Evidence: 3 Abstract : Sagittal spinal parameters pertaining to age and sex were investigated among 656 volunteers aged over 50. The deterioration originated in the pelvis among females and the cervical spine among males, which may explain the higher prevalence of cervical spondylotic myelopathy in elderly males as compared with females.